A three-dimensional placoderm (stem-group gnathostome) pharyngeal skeleton and its implications for primitive gnathostome pharyngeal architecture - Brazeau,MD; Friedman,M; Jerve,A; Atwood,RC (Journal of Morphology, 2017)
The pharyngeal skeleton is a key vertebrate anatomical system in debates on the origin of jaws and gnathostome (jawed vertebrate) feeding. Furthermore, it offers considerable potential as a source of phylogenetic data. Wellpreserved examples of pharyngeal skeletons from stemgroup gnathostomes remain poorly known. Here, we describe an articulated, nearly complete pharyngeal skeleton in an Early Devonian placoderm fish, Paraplesiobatis heinrichsi Broili, from Hunsrück Slate of Germany. Using synchrotron light tomography, we resolve and reconstruct the threedimensional gill arch architecture of Paraplesiobatis and compare it with other gnathostomes. The preserved pharyngeal skeleton comprises elements of the hyoid arch (probable ceratohyal) and a series of branchial arches. Limited resolution in the tomography scan causes some uncertainty in interpreting the exact number of arches preserved. However, at least four branchial arches are present. The final and penultimate arches are connected as in osteichthyans. A single median basihyal is present as in chondrichthyans. No dorsal (epibranchial or pharyngobranchial) elements are observed. The structure of the pharyngeal skeleton of Paraplesiobatis agrees well with Pseudopetalichthys from the same deposit, allowing an alternative interpretation of the latter taxon. The phylogenetic significance of Paraplesiobatis is considered. A median basihyal is likely an ancestral gnathostome character, probably with some connection to both the hyoid and the first branchial arch pair. Unpaired basibranchial bones may be independently derived in chondrichthyans and osteichthyans.